The role of internationalization, exports and domestic market in the fashion economy: the Brazilian footwear industry case (ModaPalavra e-periódico, 2025)
This study aims to identify the main themes and subthemes that characterize the economic dimension of the Brazilian footwear sector between January 2022 and December 2023, as well as the results, challenges and trends of the industry. Using a qualitative approach with thematic-categorical content analysis, 21 monthly reports from the Brazilian Footwear Industry Association (Abicalçados) were analyzed. The findings highlight the importance of internationalization and exports for the competitiveness of the sector. Companies with diversified strategies better face the challenges of globalization, changing consumer preferences and technological advances. Trends such as innovation in design and technology and challenges such as Asian competition and logistical issues were identified. This study combines empirical data from sectoral reports with academic theories, offering an interdisciplinary analysis of the economic transformations in the Brazilian footwear sector in the post-pandemic period. Practical implications include recommendations for companies to adopt effective internationalization strategies, innovation in design and technology, and cooperation through clusters to increase competitiveness. The study also suggests to policymakers the importance of supporting the industry with incentives and public policies that promote sustainability and innovation.
Keywords: brazilian footwear industry; iInternationalization; exports; post-pandemic economy; domestic market